Combining fractional-order PI controller with field-oriented control based on maximum torque per ampere technique considering iron loss of induction motor - Fadhil A. Hasan; Lina J. Rashad (AIMS Electronics and Electrical Engineering)
This paper presents a combined approach of fractional-order proportional-integral (FOPI) control with field-oriented control (FOC) for maximum torque per ampere (MTPA) tracking. The method maximizes the torque-to-ampere ratio by optimizing the produced torque and minimizing the stator current. This approach reduces power consumption and thereby enhances energy efficiency. Furthermore, the method is improved by considering the rotor iron loss (closest to reality). The complete mathematical analysis, modeling, and simulation are demonstrated. The dominant criteria of the motor, such as rotor speed, electromagnetic torque, and stator current, were compared with the conventional FOC technique. Results showed that the proposed approach significantly exceeds the conventional FOC in terms of drawing current and power consumption, with a 31%–47% and 35%–40% reduction in stator current and average starting current, respectively. Besides, the torque/ampere ratio increased by an average of 24%–39%, with a 12%–17% decrease in consumed kWh for a specific period. The only drawback of the proposed method is that it slightly degrades speed performance, which can simply be ignored. These findings validate the effectiveness of the proposed strategy, especially for battery-powered applications such as electric vehicles.